Case Report: p40phox deficiency underlying pediatric-onset systemic lupus erythematosus - Nieto-Patlán, Alejandro; Fernández Dávila, Natalia S.; Wang, Yuqing; Zelnick, Michelle; Muscal, Eyal; Curry, Martha; Lupski, James R.; Holland, Steven M.; Yuan, Bo; Kuhns, Douglas B.; Vogel, Tiphanie P.; Chinn, Ivan K. (Frontiers in Pediatrics, 2024)
Introduction: Systemic lupus erythematosus is a multi-faceted autoimmune disorder of complex etiology. Pre-pubertal onset of pediatric systemic lupus erythematosus (pSLE) is uncommon and should raise suspicion for a genetic driver of disease. Autosomal recessive p40 phox deficiency is a rare immunologic disorder characterized by defective but not abolished NADPH oxidase activity with residual production of reactive oxygen species (ROS) by phagocytic cells.We report the case of a now 18-year-old female with pSLE onset at 7 years of age. She presented with recurrent fever and malar rash. Aspects of her immune dysregulation over time have included typical pSLE features including production of autoantibodies, hematologic manifestations, and hypocomplementemia, as well as chronic suppurative skin lesions and recurrent infections. Genetic analysis revealed biallelic pathogenic variants in NCF4 resulting in p40 phox deficiency. Comprehensive NADPH oxidase activity studies confirmed significantly decreased production of reactive oxygen species, confirming the cellular phenotype seen in p40 phox deficient patients.Conclusions: Here, we present a patient with pSLE harboring biallelic variants in NCF4. Our patient represents a unique clinical presentation of severe onset autoimmunity in the setting of a rare inborn error of immunity affecting NADPH oxidase activity. This case underscores the need to consider genetic causes of pSLE in cases of pre-pubertal onset and atypical disease.